1981
DOI: 10.1161/01.hyp.3.6_pt_2.ii-191
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of essential hypertension.

Abstract: is not possible to study the etiology of essential hypertension without considering the role of inheritance. Unfortunately, a genetic approach to this problem has been hampered by the fact that not a single deleterious recurrent mutation has been detected in the structural idiomorphic genes which synthesize the enzymes of the renin angiotensinaldosterone and kallikrein-kinin systems in mammals. Similarly, physiologists and biochemists have been unable to discover a single polymorphic genetic system that relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Arterial blood pressure is thought to be determined by a combination of multiple genetic influences plus environmental factors and is therefore said to be multifactorial. 3 Blood pressure in children resembles that of their parents -no single factor explains this association. 4 Syncope results from faulty blood pressure control and is the final result of several mechanisms including bradycardia from excessive vagal discharge and/or lack of sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood pressure is thought to be determined by a combination of multiple genetic influences plus environmental factors and is therefore said to be multifactorial. 3 Blood pressure in children resembles that of their parents -no single factor explains this association. 4 Syncope results from faulty blood pressure control and is the final result of several mechanisms including bradycardia from excessive vagal discharge and/or lack of sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few monogenic diseases (inheritance hypertension) that have been defined as unusual hypertension. Although the available evidence strongly suggests that EH is a multifactorial inheritance disease [4], a causal gene for EH has not yet be clearly identified. There are many environmental factors that can affect EH, including obesity, diabetes, drinking and smoking.…”
Section: Definition Of Ehmentioning
confidence: 99%
“…Yet not all borderline hypertensives go on to the established phase of the disease (Julius & Esler, 1975). Cruz-Coke (1981) and others have suggested that genetics and environment interact to produce essential hypertension. In this view, genetic predisposition serves as a necessary but not generally sufficient condition for hypertension.…”
mentioning
confidence: 99%